PHENOMENCES OF TEENAGERS VANDALISM BEHAVIOR (CASE STUDY IN MEDAN CITY) - Rinaldi, Kasmanto; Praditya Nugraha, Chandra (SISI LAIN REALITA, 2021)
Vandalism is an act of harm and destroying a work of art or other valuables things, in other words is a violent and vicious destruction. There are so many cases of vandalism behaviour by teenagers that occur in the city of Medan which is to be concerns of the society . The results of this research are all forms of causative factors that motivate a teenagers in Medan City to engage the vadalism behaviour.  The research method that is used in this research is qualitative research in purpose to describe the actual situation based on what is happening on the research location through collecting, analyzing, and identifying in order to obtain an answers to the problems that have been formulated.  So this research will be conclusing a vandalism behavior that committed by the teenagers in the city of Medan is carried out by a groups and it caused by the factors that are not far from the daily lives of the teenagers, such as the influence of a bad environment, peers of the teenagers, parents, and the society environment.